The impact of financial crisis on the determinants of capital structure among Shariah constructions firms / Mohamad Nizam Jaafar ... [et al.] - Jaafar, Mohamad Nizam; Muhamat, Amirul Afif; Abdul Karim, Norzitah; Syed Alwi, Sharifah Faigah; Peie, Noraini (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2019)
The aim of this empirical study is to explore the factors that affect the capital structure of construction firms and to investigate whether the capital structure models derived from Western settings provide convincing explanations for capital structure decisions of the Malaysia firms. This study focuses on Shariah compliant construction companies since this industry has been contributing significantly towards Malaysia economic growth. In addition, this study also includes the impact of financial crisis towards firms' capital structure decision. Panel data from 11 Shariah compliant construction companies in Malaysia were analyzed for duration of 17 years (2001-2017). Different conditional theories of capital structure are reviewed i.e. trade‐off theory, pecking order theory, agency theory, and theory of free cash flow, in order to formulate testable propositions concerning the determinants of capital structure of the construction firms. The dependent variable that being used is debt ratio, while independent variables are firm size, profitability, tangible asset, growth opportunity, liquidity, and crisis respectively. Finding indicates that firm size, profitability and tangible asset are significant towards debt ratio. However, other variables including financial crisis did not have any significant impact on capital structure decision. The results of this study provide important implication to investors and manager of firms in making best decision on capital structure. This study also adds values to the existing knowledge regarding determinants of capital structure and financial crisis.